1976
DOI: 10.1111/j.1439-0329.1976.tb00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination of teleutospores of Melampsora pinitorqua Rostr.

Abstract: The germination ability of teleutospores of Melampsora pinitorqua Rostr. overwintered in different situations and under different types of soil cover was studied. The germmation period is affected by local environmental conditions. The intensity of germination of teleutospores overwintered in the underbrush is much lower than that of teleutospores overwintered on uncovered soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

1979
1979
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…The percentage of infected seedlings and the degree and localization of infection are reported in Table 1. In contrast with data obtained in 1971 (LONGO et al 1975), the results related to the rust provenance from Pizzorne showed Indeed, in their natural environment, teliospores of M. larici-tremulae were found to germinate earher in the spring than teliospores of M. pinitorqua, as was noted by LONGO et al in 1975 with respect to M. larici-tremulae at Bressanone (Bolzano) and M. pinitorqua at Monticiano (Siena), and by KURKELA (1973) for the same two rusts in Finland.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…The percentage of infected seedlings and the degree and localization of infection are reported in Table 1. In contrast with data obtained in 1971 (LONGO et al 1975), the results related to the rust provenance from Pizzorne showed Indeed, in their natural environment, teliospores of M. larici-tremulae were found to germinate earher in the spring than teliospores of M. pinitorqua, as was noted by LONGO et al in 1975 with respect to M. larici-tremulae at Bressanone (Bolzano) and M. pinitorqua at Monticiano (Siena), and by KURKELA (1973) for the same two rusts in Finland.…”
Section: Resultscontrasting
confidence: 87%
“…1). Moreover, artificial inoculations with this rust provenance (LONGO et al 1975) produced infections on Larix and some species of pine, but not on Pinus sylvestris; similar results were obtained with the rust provenance from Bressanone (Bolzano).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…32, n. 2, 1979 at five different dates representing, for this area, the periods of the formation, maturation and germination stages of rust teliospores (LONGO et al 1976). …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, owing to the partial overlapping of the host range of M. pinitorqua and M. larici-tremulae described in previous works by Longo et al (1970;1975), a basidiospore-derived direct penetration was shown also in the following cases of inoculations: 1) M. larici-tremulae on growing shoots of P. sylvestris (Longo et al 1997); 2) M. pinitorqua on growing needles from brachiblasts of Larix decidua (Moricca et al 2003); 3) M. larici-tremulae on cotyledons and primary needles of P. pinea (Moricca et al 2003).…”
Section: Introductionmentioning
confidence: 99%